Mergers and acquisitions : the case of Montepio and Finibanco - Horta, Francisca Nunes Gentil-Homem (2014)
In August of 2010 Montepio announced its intention to purchase Finibanco. Although the purchase value and estimated synergies are known from the beginning, the process to arrive at these values is not. The purpose of this work is to simulate the valuation process done by Montepio and, therefore, the data used is from end-year 2009. Valuation methods such as discounted cash-flows and market multiples will be used to value the two banks and it will be concluded that there are potential synergistic gains in this operation. Given the new financial and economic data since the conclusion of the operation, the assumptions made for the future behavior of the banks’ accounts will be revised but the main conclusion will not change: even if all the parts involved in this process had been able to know that the economic crisis was going to develop into what it is today, the operation would still be considered to be profitable. We will not arrive at a value that is close to that paid by Montepio, since we are only studying the banks of each financial group. It should be expected, however, that we arrive at smaller values than the real one, since we are considering only a part of the real operation. This is, indeed, what we will see in this work.